The risk of COVID-19 transmission upon return to sport: a systematic review - Jia, L.; Huffman, W. H.; Cusano, A.; Trofa, D. P.; Li, X.; Kelly, J. D.; Parisien, R. L. (The Physician and Sportsmedicine, 2023)
Objectives: To evaluate COVID-19 sport (RTS), as w-19 transmission rates in athletes upon return tell as the effectiveness of preventive and surveillance measures associated with RTS. Methods: In accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, the PubMed, Embase, and Cochrane Library databases were searched to identify all articles reporting on RTS during COVID-19. Articles were excluded on the basis of the following criteria: (1) non-English text, (2) only abstract available, (3) population not athlete-specific, (4) outcome not RTS-specific, (5) COVID-19 transmission data not quantified, (6) editorial, or (7) review article or meta-analysis. Study characteristics; athlete demographics; COVID-19 preventive, surveillance, and diagnostic measures; COVID-19 transmission outcomes; and RTS recommendations were collected from each included article and analyzed. Results: 10 studies were included in the final analysis, comprising over 97,000 athletes across a wide variety of sports, levels of play, and RTS settings. Of the 10 studies, eight identified low transmission rates and considered RTS to be safe/low risk. Overall, COVID-19 transmission rates were higher in athletes than in contacts, and more prevalent in the greater community than in athletes specifically. The risk of COVID-19 did not appear to be necessarily higher for athletes who played high-contact team sports, shared common facilities, or lived in communities impacted by high transmission rates, provided that rigorous COVID-19 safety and testing protocols were implemented and followed. Mask wearing and physical distancing during active play presented the greatest challenge to athletes. Conclusion: Rigorous preventive and surveillance measures can mitigate the risk of COVID-19 transmission in athletes upon RTS. However, the heterogeneity of RTS playing conditions, availability of COVID-19 resources, rise of unforeseen novel variants, and undetermined long-term impact of vaccination on athletes remain a challenge to safe and effective RTS in the era of COVID-19.